2005
DOI: 10.1021/cm0485714
|View full text |Cite
|
Sign up to set email alerts
|

Porous Polypropylene Membranes with Different Carboxyl Polymer Brush Layers for Reversible Protein Binding via Surface-Initiated Graft Copolymerization

Abstract: Photoinitiated surface-selective graft copolymerization onto polypropylene (PP) microfiltration membranes was performed using two different methods for coating the photoinitiator, benzophenone (BP), on the membrane surface. An already established adsorption method and a novel method based on preswelling of the PP in heptane, subsequent solvent exchange, and thus entrapping of the BP in the surface layer of the PP had been evaluated. With acrylic acid (AA) as the monomer, functional polymer brush structures on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
153
0
6

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 191 publications
(163 citation statements)
references
References 44 publications
3
153
0
6
Order By: Relevance
“…It is well known that excited BP can abstract hydrogen in the absence of monomer to form surface with semipinacol groups. 23,32,33 In presence of H 2 O 2 , hydroperoxide functions were generated directly on the PHBHV film via UV treatment in the presence of oxygen. Several authors have reported that hydroxyl radicals formed under UV irradiation have the ability to abstract hydrogens from the backbone of polymer producing macroradicals, which can react with the monomer to initiate grafting during the second step.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that excited BP can abstract hydrogen in the absence of monomer to form surface with semipinacol groups. 23,32,33 In presence of H 2 O 2 , hydroperoxide functions were generated directly on the PHBHV film via UV treatment in the presence of oxygen. Several authors have reported that hydroxyl radicals formed under UV irradiation have the ability to abstract hydrogens from the backbone of polymer producing macroradicals, which can react with the monomer to initiate grafting during the second step.…”
Section: Resultsmentioning
confidence: 99%
“…23,32,33 This process in two separate steps should take over better control of surface modification in comparison with free radical method developed previously because it can be considered as a ''quasi-living'' polymerization via recombination and photocleavage of semipinacol radical. 32,33 We have chosen to apply this procedure to PHBHV for grafting PHEMA either with BP as photoinitiator or H 2 O 2 to create photolabile functions on the polymer surface. Then in a second step, the functionalized films were put in contact with the monomer solution to achieve UV-initiated graft copolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…A very important issue is also the additional functionalization of membrane materials. [6] Often, membrane surfaces are post-functionalized through ''grafting-to,'' [7] ''grafting-from,'' [8] or reactive coating with polymers. [9] An alternative are additives to the membrane polymer, and special graft or block copolymers have already been found to be rather efficient in rendering the surface of porous membranes from standard engineering polymers such as poly (vinylidene fluoride) or polyethersulfone more hydrophilic and less susceptible to fouling.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Thus, the functionalized membranes have been explored for many applications according to base membrane structure and newly endowed functions. [1,11] For example, via tailored grafted functional polymeric layers on their entire surface, porous polymer base membranes are rendered waterwettable and low-fouling for filtration and fractionation processes, can been turned into highly efficient membrane adsorbers or are developed toward stimuli-responsive materials where the pores open or close upon changes of, e.g., pH value or temperature.…”
Section: Introductionmentioning
confidence: 99%